Advanced Node.js Development : Master Node.js by building real-world applications - Mead, Andrew (Packt Publishing, 2018)
Advanced Node.js Development takes your Node.js skills to the next level. The book is based on the latest release of Node (9.x) and covers advanced topics, such as building real-time web apps with Socket. IO, and reactive, asyncronous apps with Async and Await. You don't need to have read the first book in the series; any developer who knows ...